Psychopathology among offspring of parents with schizophrenia: Relationship to premorbid impairments - Keshavan, Matcheri (2008)
INTRODUCTION: A broad range of psychopathology, including externalizing disorders is seen in offspring at genetic risk for schizophrenia. However, it is unclear whether such psychopathology may underlie a higher predisposition to the premorbid antecedents of schizophrenia. We examined the prevalence and correlates of psychopathology in an ongoing study of offspring genetically at risk for schizophrenia. METHODS: Seventy five consenting high risk offspring (HR: offspring, age 15.68±3.27 years; male/female 34/41) and 82 matched comparison subjects (40 males and 42 females; age 15.92±3.0 years) participated in this study. Diagnoses were ascertained using structured psychiatric interviews and consensus meetings, including all available clinical information. RESULTS: Sixty (60%) of the HR offspring had one or more lifetime diagnosis of axis I psychiatric disorder. HR subjects with axis I psychopathology had significantly more soft neurological signs, poorer premorbid adjustment, and higher schizotypy scores as measured by Chapman psychosis proneness scales. Among those with psychopathology, HR subjects with externalizing disorders showed the most abnormal scores in schizotypy. DISCUSSION: A substantial proportion of HR offspring of parents with schizophrenia manifest a broad range of childhood psychiatric disorders. Psychopathology, especially externalizing disorders such as attention deficit hyperactivity disorder (ADHD) may represent a subgroup with an increased risk for schizophrenia spectrum disorders. This possibility needs to be examined by prospective follow-up studies, and would be of considerable importance to early diagnosis and intervention efforts in schizophrenia.